Drosophyllum lusitanicum, an endangered West Mediterranean endemic carnivorous plant: threats and its ability to control available resources - Correia, E; Freitas, H (BOTANICAL JOURNAL OF THE LINNEAN SOCIETY, 2002)
Drosophyllum lusitanicum (L.) Link (Droseraceae), Erva pinheira orvalhada, an endangered carnivorous plant, is a local endemic of clearings in pine, cork oak and oak forests or their successional shrublands in the western Iberian Peninsula and Morocco. The conservation status, distribution and population dynamics of this species are only partially known, both for Spanish and Portuguese occurrences. Portuguese distribution data from herbarium and bibliographic sources were collected for this study. Field work on 50 populations was undertaken in order to improve knowledge on their conservation status and possible threats. Natural causes, infrastructure and housing construction are stressed as the most important threats. Germination tests were carried out and the distribution patterns, plant height and the number of flowers were studied in an arbitrarily chosen population. A relatively high light requirement and low competitive ability to gain light are considered factors likely for the microdistribution pattern. Drosophyllum lusitanicum cannot compete for light in habitats with intense competition. Seeds from D. lusitanicum have reduced probability of germination when adult plants are already growing in the area. It is hypothesized that seed germination shows a similar pattern to flowering, viz over a considerable time rather than in a sudden flush. This strategy may be a key factor for the species' survival, representing attempts to take advantage of available resources, preventing intraspecific competition and, finally, preventing sudden total disappearance of a population, resulting from any catastrophic events due to natural causes or to human activity. As a result of this study, some conservation measures are suggested. (C) The Linnean Society of London.
Keywords: competition; competitive ability; Droseraceae; intraspecific competition; microdistribution pattern; Portugal; seed bank

Drosophyllum lusitanicum, an endangered West Mediterranean endemic carnivorous plant: threats and its ability to control available resources - Correia, E.; Freitas, H. (BOTANICAL JOURNAL OF THE LINNEAN SOCIETY, 2002)
Drosophyllum lusitanicum (L.) Link (Droseraceae), Erva pinheira orvalhada, an endangered carnivorous plant, is a local endemic of clearings in pine, cork oak and oak forests or their successional shrublands in the western Iberian Peninsula and Morocco. The conservation status, distribution and population dynamics of this species are only partially known, both for Spanish and Portuguese occurrences. Portuguese distribution data from herbarium and bibliographic sources were collected for this study. Field work on 50 populations was undertaken in order to improve knowledge on their conservation status and possible threats. Natural causes, infrastructure and housing construction are stressed as the most important threats. Germination tests were carried out and the distribution patterns, plant height and the number of flowers were studied in an arbitrarily chosen population. A relatively high light requirement and low competitive ability to gain light are considered factors likely for the microdistribution pattern. Drosophyllum lusitanicum cannot compete for light in habitats with intense competition. Seeds from D. lusitanicum have reduced probability of germination when adult plants are already growing in the area. It is hypothesized that seed germination shows a similar pattern to flowering, viz over a considerable time rather than in a sudden flush. This strategy may be a key factor for the species' survival, representing attempts to take advantage of available resources, preventing intraspecific competition and, finally, preventing sudden total disappearance of a population, resulting from any catastrophic events due to natural causes or to human activity. As a result of this study, some conservation measures are suggested. (C) The Linnean Society of London.
The following values have no corresponding Zotero field: pub-location: 24-28 OVAL RD, LONDON NW1 7DX, ENGLAND publisher: ACADEMIC PRESS LTD ELSEVIER SCIENCE LTD
Keywords: competition; competitive ability; Droseraceae; intraspecific competition; microdistribution pattern; Portugal; seed bank